Implementasi Logika Fuzzy Metode Tsukamoto dalam Menentukan Tingkat Resiko Terkena Serangan Jantung - Puti Andam Dewi; Yusmet Rizal (Journal of Mathematics UNP, 2020)
Abstract—A coronary artery is a system of blood vessels that supplies oxygen and nutrients to the heart muscle. If there is narrowing, blood flow to the heart will decrease and cause a heart attack. This situation will not occur if you avoid the factors that trigger heart attacks. The formulation of the problem is how to determine the level of risk of having a heart attack using the Tsukamoto method of fuzzy logic. The purpose of this study was to find out how to determine the level of risk of having a heart attack using the Tsukamoto method of fuzzy logic. This research is an applied research with the population is patients who seek treatment at the cardiac clinic of Semen Padang Hospital, while the sample is outpatient cardiac clinic Semen Padang Hospital. The type of data is secondary data consisting of age, blood pressure, blood sugar and total blood cholesterol data. The results of this study are the level of risk of having a heart attack in the outpatient cardiac clinic at Semen Padang Hospital. By substituting all the values of the triggering factors, the risk of heart attack is obtained.Keywords—Heart Attack, Influencing Factors, Fuzzy Logic, Tsukamoto Method